الاستهلاك العائلي والنظريات المفسرة له - ضو, نصر (جامعة الوادي - University of Eloued, 2013)
Consumption economic phenomenon practiced by economists agents to achieve their desires and their basic needs by the different social and functional status, and the evolution of his concept of the age to another due to the evolution of economic ideas, no matter how different aspects of the multiplicity of views on the concept of consumption in economic theory. Also interested in this phenomenon, researchers and economic theorists great interest, and tried to be interpreted as being related to other economic phenomena, such as income and demographic growth and the general level of prices and other phenomena, to be multiple theories that explain their different environment and culture of each researcher or thinker over time and the historical development of this phenomenon.
مقال
Keywords: :الاستهلاك، العائلة، الاستهلاك العائلي، النظرية الكينزية، الدخل، نظريات الاستهلاك، قوانين انقل; Consumption, family, household consumption, Keynesian theory, income, consumption theories, transfer laws